The Effect of ROE, DER, and EPS on Stock Prices of IDX Energy Companies (2020–2024) - Farhatul Azizah; Acep Komara (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
This study examines the effects of Return on Equity (ROE), Debt to Equity Ratio (DER), and Earnings per Share (EPS) on the stock prices of companies in the IDX Energy sector during the 2020–2024 period. The research is motivated by the high volatility in the energy sector due to the COVID-19 pandemic, post-pandemic recovery, and global commodity price fluctuations, which may influence investor responses to firm fundamentals.Using a quantitative approach, this study analyzes secondary data from 15 companies selected through purposive sampling, resulting in 75 firm-year observations. The data were analyzed using panel data regression.The results show that ROE and DER have positive but statistically insignificant effects on stock prices, while EPS has a positive and statistically significant effect. Simultaneously, all variables significantly affect stock prices, with the model explaining 56.45% of the variation.These findings indicate that EPS is the most relevant financial indicator in explaining stock price movements of IDX Energy companies during the study period.